Prototype Modeling of Bed for Bedridden Patients - Bunkum, Manao; Reanaree, Parkbhum; Wanluk, Nutthanan; Visitsattapongse, Sarinporn (My University, 2019)
One of the most common health risks for bedridden patient is a pressure sore or decubitus ulcers. Pressure sore developed in people who are not able to move or lying in the same position for a long period of time. To solve this problem, a caregiver must change the patient's position every two hours if possible. In addition, the caregiver already has many kinds of care work to assist the patient such as changing clothes, administering medicine, daily health checking etc. This paper presented a design model of the bed used for bedridden patients, including paralysis, individuals with impaired mobility, and the elderly. The bed consists of an automatic bed lift control system and a patient monitoring system. The bed can change the patient's position in left or right tilt by lifting the left or right side of the bed up automatically. The system came with a graphic user interface to communicate with the caregiver or physician. The patient monitoring system including, the heart rate monitor, the body temperature monitor and the blood pressure monitor which are then sent to a home or hospital server. All data can then be remotely monitored by caretaker or physician. The proposed of the bed is designed to better assist the daily life of bedridden patients and caregivers.
Keywords: Bedridden patient; Patient bed; Pressure sure